The Influence of Psychological Capital on Readiness for Change in Teachers, with Professional Learning Community as Moderator - Lissa Pratiwi; Endang Parahyanti (Journal of Social Research, 2025)
Based on data from the Ministry of Education and Culture in 2024, there is a difference in the implementation and learning outcomes of the Independent Curriculum between the secondary school level and the elementary school level. School readiness, one of which is the capacity of teachers, is a factor in this difference. From previous research, an individual's capacity to be ready to change affects an organization's readiness to face change. This study aims to see the influence of Psychological Capital on Readiness for Change with the Perception of the Effectiveness of the Professional Learning Community as a moderator. Participants are 143 high school teachers (SMP/SMA/SMK/equivalent) who have been active in the Professional Learning Community in the past year, either MGMP or Learning Community. Sampling with non-probability sampling, specifically convenience sampling. The measurement tools used are the Readiness for Change Scale (Hanpachern, 1997), the Psychological Capital Questionnaire (PCQ-12) (Luthans et al., 2007), and the Professional Learning Community Assessment-Revised (PLCA-R) shorter version (Moosa et al., 2020). The results of the regression test with Hayess' macro-PROCESS Model 1 show that Psychological Capital has a positive and significant influence on Readiness for Chang. However, the Professional Learning Community cannot moderate the influence of Psychological Capital on Readiness for Change. Interventions on Psychological Capital, for example in the form of training, can be carried out by both school management and policy makers in education to increase teachers' readiness to change, especially in this era of highly dynamic educational change.